Nilai Pendidikan Karakter Dalam Film Big Brother Karya Kam Ka-Wai - Melinda Melinda; Patrisia Cuesdeyeni; Alifiah Nurachmana; Albertus Purwaka; Misnawati Misnawati (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
The purpose of this study was to describe the character education values of responsibility, curiosity, hard work, respect for achievement, social care, and friendship/communicativeness in Kam Ka-Wai's Big Brother film. This study uses a descriptive qualitative approach, in which the researcher records carefully and accurately the data in the form of words, sentences, pictures, and videos contained in the film. The use of a descriptive qualitative approach in this study aims to describe the values of character education, namely responsibility, curiosity, hard work, respect for achievement, social care and communicative/friendly in the Big Brother film. The value of responsibility character education in the film Big Brother consists of 4 data. The educational value of the character of curiosity in the Big Brother film consists of 5 data. The value of hard work character education in the film Big Brother consists of 7 data. The value of character education appreciating achievement in the Big Brother film consists of 4 data. The value of social care character education in the film Big Brother consists of 12 data. The value of friendly/communicative character education consists of 4 data.